Patterns of torture among forcibly displaced Eritreans in California: A cross-sectional study - P. Suzanne Portnoy; Alejandro Diaz; Jenna Kupa; Isabelle Rocroi; Emily Tatel; Kala Mehta; Nicholas Nelson (Torture)
Abstract